The Arab-Byzantine Struggle in the 10th Century in the Light of "Synopsis chronike" by Constantine Manasses (Phantom of Muhammad, Shade of Samuel Byzantine Empire in Relation to Members of Other Cultures and Religions (7th–15th c.): No. XXXIX, 2020)
Artykuł jest poświęcony obrazowi zmagań arabsko-bizantyńskich – za panowania Romana II, Nicefora II Fokasa I Jana Tzymiskesa – w Przeglądzie historii Konstantyna Manassesa (XII w.).